Hybrid Wavelength Switched-TDMA High Port Count All-Optical Data Centre Switch - Funnel, Adam; Shi, Kai; Costa, Paolo, Philip Watts; Ballani, Hitesh; Thomsen, Benn (OSA Journal of Lightwave Technology, 2017)
The physical layer, data plane design of an all-optical network switch capable of scaling to 1024 ports at 25 Gb/s per port is presented and experimentally evaluated. Fast tuning DSDBR lasers modulated with line-coded bipolar data allow combined wavelength switching and TDMA to provide packet switch-like functionality with over 2 Tb/s of total switch bandwidth. A passive fibre star coupler core with high sensitivity, DSP-free coherent receivers creates a low complexity, easily upgradeable building block for data centre networks.